Cornelis Springer as topographer? (Bulletin KNOB, 1991)
Cornelis Springer (1817-1891) was an important townscape painter. Archives collect his drawings because of their topographical indications. However, in Springer's oeuvre the artist and the topographer contend for the mastery. Do his paintings and drawings really contain documentary value?This article discusses some image-conventions typical of Springer and makes a comparison with several works of other artists Springer showing dependence of these examples. Thus one of the principles he applied to his paintings is the insertion of a building, drawn after reality, into an invented environment. The principle of removal is related to the principle of insertion. Here different topographical elements are brought together in one representation. Converting, or the placement of small alterations in extant architecture is a very general principle in Springer's oeuvre.Even more than converting the proportioning of buildings is characteristic of Springer's way of painting. Archaisement is the last principle he applied to his townscapes. Being a romanticist Springer liked to place his representations in a Dutch 17th century setting. All five of these principles detract from the likeness of the represented architecture.The methods Springer applied rendering extant architecture not only differs in their measures of radicality, but also in frequency. Sometimes even two or more of these principles were combined in one painting at the same time. Apart from these personal methods Springer also borrowed principles and motifs from the oeuvre of other artists.Kaspar Karsen (1810-1896) was his most important teacher. Therefore Springer's early oeuvre is clearly influenced by Karsen. On the occasion of the Rembrandt festivities (1852) Karsen and Springer painted a sight of The Hague in an archaizing 17th century fashion. A lithograph of Jan Weissenbruch (1822-1880) however is the real example.Lithographs of the English artist Samuel Prout (1783-1852) both and the oeuvre of H.P. Schouten (1747-1822) and C. Pronk (1691-1759) inspired Springer to copying these townscapes as well, although the upholstering of the representations mostly is Springer's own. Thus the oeuvre of Cornelis Springer cannot be used as a source for topographical study in its own right.His numerous sketchbooks prove that Springer in any case strove to give his townscapes a topographical content. His methods on the other hand contradict this supposition. Springer's oeuvre is being characterized by a longing for an ideal image rather than a resembling representation of reality. In his entire career Springer has been dominated by the nostalgic ideal of the small 17th century Dutch town.The transition from invented to recognizable townscapes did not change this idealistic character of his oeuvre. The topographical element was subordinated to the pleasant imaginary setting. Often several topographical elements are united. Sometimes Springer's representations are based on other works of art. In the 19th century copying other artist's compositions probably was not unusual at all.